Fluorescence‐detected XAS with sub‐second time resolution reveals new details about the redox activity of Pt/CeO2 catalyst. (30th May 2018) - Guda, Alexander A.; Bugaev, Aram L.; Kopelent, Rene; Braglia, Luca; Soldatov, Alexander V.; Nachtegaal, Maarten; Safonova, Olga V.; Smolentsev, Grigory
Abstract : A highly sensitive setup for measuring fluorescence‐detected X‐ray absorption spectroscopy with sub‐second time resolution has been developed at the SuperXAS beamline at the Swiss Light Source. This opens new opportunities for understanding the dynamic structure of heterogeneous catalysts. Abstract : A setup for fluorescence‐detected X‐ray absorption spectroscopy (XAS) with sub‐second time resolution has been developed. This technique allows chemical speciation of low‐concentrated materials embedded in highly absorbing matrices, which cannot be studied using transmission XAS. Using this setup, the reactivity of 1.5 wt% Pt/CeO2 catalyst was studied with 100 ms resolution during periodic cycling in CO‐ and oxygen‐containing atmospheres in a plug‐flow reactor. Measurements were performed at the Pt L 3 ‐ and Ce L 3 ‐edges. The reactivity of platinum and cerium demonstrated a strong correlation. The oxidation of the catalyst starts on the ceria support helping the oxidation of platinum nanoparticles. The new time‐resolved XAS setup can be applied to various systems, capable of reproducible cycling between different states triggered by gas atmosphere, light, temperature, etc . It opens up new perspectives for mechanistic studies on automotive catalysts, selective oxidation catalysts and photocatalysts.